Cost-effectiveness analysis of cefazolin and clindamycin in postpartum patients at PKU Muhammadiyah Hospital Yogyakarta - Anggita Esa Putri Fitrichia; Susan Fitria Candradewi; Dewi Inggit Karnasi; Adnan Adnan (Universitas Muhammadiyah Malang, 2021)
Postpartum infections can occur after normal or cesarean delivery. Proper administration of antibiotics can reduce the risk of postpartum infection The occurrence of postpartum infections can increase the cost of childbirth. The purpose of this study is to find out the cost-effectiveness of antibiotic therapy at PKU Muhammadiyah Hospital Yogyakarta. This study was retrospective observational and was conducted during October to December 2020. The inclusion criteria in this study were postpartum patients who received cefazolin and clindamycin therapy and were over 20 years old, while the exclusion criteria in this study were patients who died, had incomplete data, and had complications of the disease. The effectiveness of antibiotic therapy was measured from the clinical outside of body temperature and length of hospitalization. Cost-effectiveness were assessed from ACER (Average Cost-effectiveness Ratio) and ICER (Incremental Cost-effectiveness Ratio). The results showed that the effectiveness of antibiotics based on the clinical outcome temperature and length of cefazolin of 81.3% and 2.7 days while in clindamycin by 18.8% and 1.8 days. The ACER (Average cost effectiveness ratio) based on the clinical output of body temperature in both groups was IDR 64,348 (cefazolin) and IDR 98,319 (clindamycin). ACER values based on long of stay (LOS) clinical discharge in both groups amounted to IDR 19,375 (cefazolin) and IDR 10,268 (clindamycin). The value of ICER (Incremental Cost- effectiveness Ratio) cefazolin against clindamycin based on the clinical output of temperature and length of hospitalization (LOS) respectively is IDR 54,129 and IDR 37,590 for each effectiveness achieved. The conclusion of this study is that the use of cefeazoline is more therapeutically effective than clindamycin with greater therapeutic costs.